A Project feasibility study on Philippine Industrial Engineering Consultancy Group - Atutubo, Janet; Bucaycay, Jocelyn; Chio, Anne Michelle; Dujunco, Mildred; Gonzales, Ma. Pinky (College of Engineering, 1991)
Market Study: The project concerned is an Industrial Engineering Consultancy firm that offers services such as: systems analysis, production audit, operations research, management information systems, engineering economy and the project feasibility analysis. The firm's target market area is a share (5%) of the total Small and Medium Scale Enterprises - identified through the conducted market survey - willing to avail of the firms resources. The SME sector is forecasted to increase due to growing government support. The sole practitioners and regional consultancy firms are the recognized direct competitors and the direct marketing approach - cold calls and referrals - is to be employed by the firm. The firm is competitively positioned considering that not only will it employ competent consultants and research associates but will also price it's services taking into consideration the client's financial capability. Technical Study: The proposed consultancy firm will utilize the standard operating procedure as well as the corresponding specific procedures for each Industrial Engineering technique. The firm's capacity is obtained through the combined work of five part time consultants and then full time research associates. The consultants are expert in the field of Industrial Engineering and possess outstanding academic and technical skills as well as work experience in the five different fields mentioned earlier. They are preferably graduates of a Masters degree in IE. As for the Research Associates they will be fresh graduates of reputable schools like UP, Ateneo de Manila, De La Salle, UST and MIT. Each project will last from two to three months depending on the size of the project. Free seminars will occasionally be conducted during the first few years of operation. The firm will rent an office space be located in J & S Building at the back of Quezon City hall or in other less expensive office in Quezon City due to its proximity to probable clients as well as support industries and services.